Multi-Period Coordination Mechanism Based on Revenue Sharing Contract in VMI Model (Advances in Applied Mathematics and Mechanics, 2019)
Vendor Managed Inventory (VMI) model coordinates the supply chain, for the vendor is authorized to manage retailer's inventory and revenue-sharing contract helps to achieve the coordination. In this paper, a multi-period two-echelon supply chain coordination model, which is composed of a manufacturer and a retailer, is built. Under the assumption that the market demand rate is affected by time, sales price and the current inventory level, the supply chain profit models of centralized decision and decentralized decision based on VMI model are established respectively, with optimal decisions obtained in each model. Furthermore, the revenue sharing contract is used to synchronize the supply chain in the VMI model and in turn the analytical model in the supply chain to achieve Pareto improvement is obtained. An equation describing thin film oscillating is used to correct the profit value in VMI model to simulate the reality. Finally, a numerical illustration validating the model and analytical results showing parameters' varying effects on the profit and optimal quantity of each party, are presented. The results demonstrate that the revenue sharing contract is able to simultaneously improve the interests of parties in the multi-period VMI supply chain.